Weaker Interactions in Zn2+ and Organic Ion‐pre‐intercalated Vanadium Oxide toward Highly Reversible Zinc‐ion Batteries. Issue 4 (21st December 2020) - Zhang, Feng; Sun, Xiucai; Du, Min; Zhang, Xiaofei; Dong, Wentao; Sang, Yuanhua; Wang, Jianjun; Li, Yanlu; Liu, Hong; Wang, Shuhua
Abstract : Driven by safety issues, environmental concerns, and high costs, rechargeable aqueous zinc‐ion batteries (ZIBs) have received increasing attention in recent years owing to their unique advantages. However, the sluggish kinetics of divalent charge Zn 2+ in the cathode materials caused by the strong electrostatic interaction and their unsatisfactory cycle life hinder the development of ZIBs. Herein, organic cations and Zn 2+ ions co‐pre‐inserted vanadium oxide ([N(CH3 )4 ]0.77, Zn0.23 )V8 O20 ·3.8H2 O are reported as the cathode for ultra‐stable aqueous ZIBs, in which the weaker electrostatic interactions between Zn 2+ and organic ion‐pinned vanadium oxide can induce the high reversibility of Zn 2+ insertion and extraction, thereby improving the cycle life. It is demonstrated that ([N(CH3 )4 ]0.77, Zn0.23 )V8 O20 ·3.8H2 O cathodes deliver a discharge capacity of 181 mA h g −1 at 8 A g −1 and ultra‐long life span (99.5% capacity retention after 2000 cycles). A reversible Zn 2+ /H + ions (de)intercalation storage process and pseudocapacitive charge storage are characterized. The weaker interactions between organic ion and Zn 2+ open a novel avenue for the design of highly reversible cathode materials with long‐term cycling stability. Abstract : The ([N(CH3 )4 ]0.77, Zn0.23 )V8 O20 ·nH2 O was synthesized via a one‐step hydrothermal reaction. Due to the insertion of organic ions, zinc–carbon interactions were formed in the cathode materials. Compared with the Zn–O interactions in traditional vanadium oxides, weak Zn–C interactions can promote reversible Zn 2+ insertion/extraction and improve the reversible cycling performance of the TMAVO.